Evaluations of alleged torture and ill treatment in Thailand: A collection of forensic medical evidence by non-medical evaluators. (October 2020) - Moreno, Alejandro; Lin, James; Iacopino, Vincent
Abstract: Forensic medical evidence plays a critical role in the investigation and documentation of torture and ill treatment, as well as in civil reparation cases and in state monitoring mechanisms, especially if conducted on a timely basis by qualified, impartial experts. Detainees in many countries, such as Thailand, face significant barriers to access medical personnel while in custody or independent, non-governmental or impartial forensic experts. This study summarizes an effective method of collecting forensic medical evidence of torture and ill treatment by non-medical evaluators under conditions of limited access to detainees. The aim of the study was to determine the feasibility to render an expert opinion based on such documentation. We reviewed 49 non-medical forensic evaluations of alleged torture and ill treatment conducted by 11 attorneys or legal representatives in Southern Thailand between March and October 2011. Forty-four non-medical evaluations (90%) had sufficient information for the authors to formulate an opinion between the alleged abuse and the documented findings and to make a statement as to the level of consistency between them. Of these 44 evaluations, the authors determined that in 28 (70%) cases, the documented findings were highly consistent with the alleged abuse and in 13 (30%) cases, the documented findings were consistent with the alleged abuse. The study shows that non-medical evaluations conducted by attorneys and legal advocates can be a resource when individuals are denied access to forensic medical expertise. The results of a non-medical evaluation interpreted by an expert can have great evidentiary value when courts are reluctant to entertain writs of protection, such as a habeas corpus, or when states are reluctant to meet their obligations to pursue formal forensic evaluations. Highlights: Forensic evidence plays a critical role in corroborating allegations of torture. Detainees often have limited access to impartial forensic medical evaluators. Experts had information to formulate an opinion in 90% of non-medical evaluations. Non-medical evaluations can serve as the basis for an expert opinion in court.